Aspectos demográficos de Chrysomya albiceps (W.) (Diptera: Calliphoridae): análise de sensibilidade dos fatores de mortalidade no estágio imaturo e parâmetros demográficos de adultos - Silva, Eveline da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In their natural environment, many invertebrates and vertebrates use discrete and ephemeral substrates for feeding and laying their eggs or larvae, and among them, could be cited the blowfly Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae). Accidentally introduced in the Americas in the mid -1970s, C. albiceps has caused the population decline in native species as Lucilia eximia and Cochliomyia macellaria. For blowflies, the larval stage is the main period in which competition for limited food resources occurs, with individuals competing intensely for resources in an attempt to ingest as much food as possible before the complete depletion of the resources. The result of this competition is seen on population parameters as survival, fecundity and size of the resulting adults, with direct effects on the population dynamics of the species involved. Therefore, the population density of immature in the food substrate becomes a primary factor in studies about population dynamics, because it influences directly the competition and hence the variation of these population parameters. In this study were analyzed aspects of the ecology of C. albiceps using experimental populations. The results of this study indicate that the initial larval density influences the demography and the viability and fecundity of populations of C. albiceps ; initial high density can improve the feeding process and reduce development time at the immature stage. The initial larval mortality has great influence on life expectancy at the time of adult emergence. 200 was optimal density for developing species. Adults from the densities 800 and 100 had low values for survival and life expectancy. Females were longer-lived than males (e0 higher for females), and males tend to die more in the early ages (H higher for males). At density 800, food shortages resulted in small adults and females with low fecundity. In the opposite situation, density 100, in which the quantity...

Em seu ambiente natural, muitas espécies animais, invertebrados e vertebrados, utilizam substratos discretos e efêmeros para sua alimentação e postura de ovos ou larvas, e dentre elas está a espécie de mosca-varejeira Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae). Introduzida acidentalmente no continente americano em meados da década de 70, tem causado o declínio de populações de califorídeos nativos como Lucilia eximia e Cochliomyia macellaria. Em moscas-varejeiras, o período em que ocorre a maior limitação de recursos alimentares é durante o estágio larval, com indivíduos competindo intensamente pelos recursos na tentativa de ingerir a maior quantidade de alimento antes que os recursos se esgotem por completo. Os resultados da competição por recursos alimentares limitados durante o estágio imaturo podem ser vistos em parâmetros como sobrevivência, fecundidade e tamanho dos adultos resultantes, e estes têm efeitos diretos sobre a dinâmica populacional da espécie envolvida. Portanto, a densidade populacional de imaturos no substrato alimentar se torna um fator primordial nos estudos sobre a dinâmica populacional, pois influencia diretamente a competição e, consequentemente, a variação desses parâmetros. Neste estudo, foram analisados aspectos da ecologia populacional de C. albiceps utilizando populações experimentais. Os resultados do presente estudo indicam que a densidade larval inicial tem influência sobre aspectos da demografia e sobre a viabilidade e fecundidade de populações de C. albiceps; altas densidades iniciais podem melhorar o processo de alimentação nas larvas e diminuir o tempo de desenvolvimento no estágio imaturo. A mortalidade larval inicial tem grande influência na expectativa de vida no momento da emergência dos adultos. A densidade 200 foi a densidade ótima para o desenvolvimento da espécie. Adultos das densidades 800 e 100 apresentaram baixa sobrevivência e expectativa de...
Keywords: Diptera; Diptero; Chrysomya albiceps; Animais - População; Modelos matematicos; Competição (Biologia); Ecologia de populações; Chrysomya albiceps - Mortalidade; Densidade demografica